THE INFLUENCE OF WORK DISCIPLINE, WORK MOTIVATION, AND LEADERSHIP SUPPORT ON THE CAREER DEVELOPMENT OF INDONESIAN NATIONAL POLICE PERSONNEL IN THE ICT DIVISION: THE ROLE OF EDUCATION AND DEVELOPMENT AS INTERVENING VARIABLES - Robiah; Joseph MJ Renwarin; Bungaran Saing (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to analyze the influence of work discipline, work motivation, and leader support on the career development of Indonesian National Police (Polri) personnel, with education and training as an intervening variable. The research employed a quantitative approach through a survey method using Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. The results indicate that work discipline, work motivation, and leader support have a positive and significant effect on education and training, as well as on career development. Education and training were proven to mediate these relationships. These findings emphasize the importance of strengthening discipline, motivation, and leadership support, as well as optimizing education and training programs to support career development among Polri personnel.